Factorise: 25(2x + Y)2 - 16(X - Y)2 - Mathematics

Advertisement Remove all ads
Sum

Factorise: 25(2x + y)2 - 16(x - y)2 

Advertisement Remove all ads

Solution

25(2x + y)2 - 16(x - y)2 

= [5(2x + y)]2 - [4(x-y)]2

= (10x + 5y)2 - (4x - 4y)2

= (10x + 5y + 4x - 4y) (10x + 5y - 4x + 4y)

= (14x + y)(6x + 9y)

= (14x + y) 3(2x + 3y)

= 3 (14x + y)(2x + 3y)

Concept: Factorisation by Difference of Two Squares
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 13 Factorisation
Exercise 13 (C) | Q 11 | Page 159
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×